Lack of association between the P413L variant of chromogranin B and ALS risk or age at onset: a meta-analysis. Issue 1 (2nd January 2018) - Yang, Xinglong; Li, Shimei; Xing, Dongmei; Li, Peiyun; Li, Ci; Qi, Ling; Xu, Yanming; Ren, Hui
Abstract: Background : Amyotrophic lateral sclerosis (ALS), the most common motor neuron disease, is thought to result from interaction of genetic and environmental risk factors. Whether the potentially functional exonic P413L variant in the chromogranin B gene influences ALS risk and age at onset is controversial. Method : We meta-analysed or other studies assessing the association between the P413L variant and ALS risk or age at ALS onset indexed in Web of Science, PubMed, Embase, Chinese National Knowledge Infrastructure, Wanfang, and SinoMed databases. Results : Five case-control studies were analysed, involving 2639 patients with sporadic ALS, 201 with familial ALS and 3381 controls. No association was detected between risk of either ALS type and the CT + TT genotype or T-allele of the P413L variant. Age at ALS onset was similar between carriers and non-carriers of the T-allele. Conclusion : The available evidence suggests that the P413L variant of chromogranin B is not associated with ALS risk or age at ALS onset. These results should be validated in large, well-designed studies.